Características antropométricas e posturais de pés de idosos diabéticos e não diabéticos: evolução no período de quatro anos - Aquino, Victor da Silva (Universidade Federal de São Carlos, 2012)
The aging of the population is a phenomena observed in the whole planet. Brazil follows this tendency with 21 million elderly, who correspond to 11,3% of the population. The projection is that in the year 2025 the population of elderly in Brazil will increase 16 times against five times the total population reaching, in absolute values, the sixth position in elderly population in the world. Close to 10 to 15% of the Brazilian population with age superior to 50 years has Diabetes Mellitus12. Due to the lack of studies which observed the behavior of anthropometric and postural measures in elderly diabetic in the long term, the objective of this paper was to investigate, in the period of 4 years, which anthropometric and postural alterations occur in the feet of elderly diabetic and, compare them with non-diabetic elderly. Four hundred and three individuals with 60 years of age or more were contacted, who participated of the study previous to 2006, of which 165 accepted to participate again. In this way, the current paper had four groups of participants, Diabetics 2006 (72), Diabetics 2010 (26), Non-Diabetics 2006 (331) and Non-Diabetics 2010 (139). All the participants answered an interview-questionnaire that contemplated social aspects, orthopedic investigation and the presence of pain. At the end of each evaluation the individual was invited to a re-evaluation after one week, with the purpose of verifying the trustworthiness of the measurements carried out by the same examiner at different moments. For the analysis of the anthropometric variables and of Arch Index, between the years 2006 and 2010, the groups were composed of 165 individuals, of which 26 were diabetic and 139 non-diabetic. On the other hand, for the Foot Posture Index IPP and its six criteria, groups of Diabetics were composed of 72 individuals in 2006 and 26 in 2010; and for comparison in the Non-diabetics, the 2006 group was composed of 331 individuals and the 2010 group of 139. The characterization of the sample was made by means of descriptive analysis, with central tendency and dispersion measures. Throughout 4 years, a reduction of the Length of the feet, reduction in the Height of the 1st Finger, of the Angle of the 1st Metatarsofalangeana Articulation was found between the Diabetics and Nondiabetics. There was also an increase in the Arch Index in the same period in both groups. In the comparison of the postural variables, the group of Non-diabetics changed more than the Diabetics group. The changes that occurred were, an increase of the percentage of neutral feet and a reduction in the alterations.
Keywords: Fisioterapia; Antropometria; Pés - doenças; Diabetes mellitus; Envelhecimento; Idosos; Doenças do Pé; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL